Pathology informatics fellowship training: Focus on molecular pathology - Diana Mandelker (Journal of Pathology Informatics, 2014)
Background: Pathology informatics is both emerging as a distinct subspecialty and simultaneously becoming deeply integrated within the breadth of pathology practice. As specialists, pathology informaticians need a broad skill set, including aptitude with information fundamentals, information systems, workflow and process, and governance and management. Currently, many of those seeking training in pathology informatics additionally choose training in a second subspecialty. Combining pathology informatics training with molecular pathology is a natural extension, as molecular pathology is a subspecialty with high potential for application of modern biomedical informatics techniques. Methods and Results: Pathology informatics and molecular pathology fellows and faculty evaluated the current fellowship program′s core curriculum topics and subtopics for relevance to molecular pathology. By focusing on the overlap between the two disciplines, a structured curriculum consisting of didactics, operational rotations, and research projects was developed for those fellows interested in both pathology informatics and molecular pathology. Conclusions: The scope of molecular diagnostics is expanding dramatically as technology advances and our understanding of disease extends to the genetic level. Here, we highlight many of the informatics challenges facing molecular pathology today, and outline specific informatics principles necessary for the training of future molecular pathologists.